Growth reconstitution following antiretroviral therapy and nutritional supplementation. (24th September 2015) - McGrath, Christine J.; Diener, Lara; Richardson, Barbra A.; Peacock-Chambers, Elizabeth; John-Stewart, Grace C.
<x xml:space="preserve">Abstract</x> Objective: As antiretroviral therapy (ART) expands for HIV-infected children, it is important to determine its impact on growth. We quantified growth and its determinants following ART in resource-limited (RLS) and developed settings. Design: Systematic review and meta-analysis. Methods: We searched publications reporting growth [weight-for-age (WAZ), height-for-age (HAZ), and weight-for-height (WHZ) z scores] in HIV-infected children following ART through August 2014. Inclusion criteria were as follows: younger than 18 years; ART; at least 20 patients; growth at ART; and post-ART growth. Standardized and overall weighted mean differences were calculated using random-effects models. Results: A total of 67 articles were eligible (RLS = 54; developed settings = 13). Mean age was 5.8 years, and comparable between settings (P = 0.90). Baseline growth was substantially lower in RLS vs. developed settings (WAZ −2.1 vs. −0.5; HAZ −2.2 vs. −0.9; both P < 0.01). Rate of weight but not height reconstitution during 12 and 24 months was higher in RLS (12-month WAZ change 0.84 vs. 0.17, P < 0.01). Growth deficits persisted in RLS after 2 years ART (P = 0.04). Younger cohort age was associated with greater growth reconstitution. Protease inhibitor and nonnucleoside reverse-transcriptase inhibitor regimens yielded comparable growth. Adjusting for age and setting, cohorts with nutritional supplements had greater growth gains (24-month rate difference: WAZ 0.55, P = 0.03; HAZ 0.60, P = 0.007). Supplement benefits were attenuated after adjusting for baseline cohort growth. Conclusion: RLS children had substantial growth deficits compared with developed settings counterparts at ART; growth shortfalls in RLS persisted despite reconstitution. Earlier age and nutritional supplementation at ART may improve growth outcomes. Scant data on supplementation limit evaluation of impact and underscores need for systematic data collection regarding supplementation in pediatric ART programmes/cohorts.